2020
DOI: 10.2174/1570193x16666190508091231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Applications of Dicationic Ionic Liquids in Organic Synthesis

Abstract: Dicationic ionic liquids are an emerging group of Ionic Liquids (ILs) that are currently receiving much attention as green reaction media and catalysts. Because of a great number of possible combinations of cations and anions, the physical and chemical properties of dicationic ionic liquids are more tunable and broader than monocationic ILs. Therefore, their unique properties have made them the target of many applied and fundamental researches. Actually, dicationic ionic liquids are more effective and rather f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Due to their unique properties, dicationic ILs (DILs) have been widely used in thermal storage [67,129], organic synthesis [130], anti-corrosion [131], or as surface-active agents [132], and they are less toxic than their monocationic counterparts [133]. Figure 16.…”
Section: Dicationic Ilsmentioning
confidence: 99%
“…Due to their unique properties, dicationic ILs (DILs) have been widely used in thermal storage [67,129], organic synthesis [130], anti-corrosion [131], or as surface-active agents [132], and they are less toxic than their monocationic counterparts [133]. Figure 16.…”
Section: Dicationic Ilsmentioning
confidence: 99%
“…ILs present interesting properties, such as low vapor pressure, high thermal, chemical, and electrochemical stability, being non-flammable [5][6][7], and the ability to dissolve or extract several chemicals (organics and inorganics; polar and nonpolar) [8], and can be used in separations [9] or as catalysts, among other important properties [10][11][12]. It should be noted that these characteristics are not common to all ionic liquids, and properties depend on the ions.…”
Section: Deep Eutectic Solvents (Dess)mentioning
confidence: 99%
“…This mini-review is focused on the organocatalytic applications of imidazolium-based DILs, also associated with polymers, nanomaterials, and various composites reported in the literature in the last six years; this specific research field being very recent. To the best of our knowledge, only two recent reviews are reported in the literature about the properties and application of DILs; however, these documents do not specifically treat organocatalysis and do not extensively review the DILs use in organic synthesis from 2016 onwards [ 12 , 13 ]. We thus decided to start from these two reviews, reporting the results of DILs organocatalysis from 2016.…”
Section: Introductionmentioning
confidence: 99%